RAS-pathway mutation patterns define epigenetic subclasses in juvenile myelomonocytic leukemia - Daniel B. Lipka; Tania Witte; Reka Toth; Jing Yang; Manuel Wiesenfarth; Peter Nöllke; Alexandra Fischer; David Brocks; Zuguang Gu; Jeongbin Park; Brigitte Strahm; Marcin Wlodarski; et al. (Nature Communications, 2017)
Juvenile myelomonocytic leukemia (JMML) is an aggressive disease with limited options for treatment. Here, the authors analyse the DNA methylome and mutational profile of JMML to define three subgroups with unique molecular and clinical characteristics.